A guide to behaviour change communication in improving reproductive and sexual health of young and adolescents (World Population Foudation (WPF), 2007)
The guide was developed based on current materials of BCC and RH/SH education for young people as well as on valuable expreiences in Vietnam and in the world. This guide consists of 3 books: 1. Concepts, skills of planning and implementing behaviour change communication activities ; 2. Objectives of behaviour change communication in the Rhiya Vietnam programme ; and 3. Handout for participants.